Estimating carbon nanotube length from isotropic cloud point of carbon nanotube/chlorosulfonic acid solutions. (September 2021) - Lee, Haemin; Cho, Hyunjung; Lee, Sung-Hyun; Lee, Dong-Myeong; Oh, Eugene; Lee, Jaegeun; Lee, Kun-Hong
Abstract: The information about CNT lengths is essential to realize the unique properties of CNTs at the macroscopic scale. Here, we experimentally demonstrate a short-cut method to characterize the average length of carbon nanotubes (CNTs) based on the isotropic-cloud point ( ϕ ICP ) of CNT/chlorosulfonic acid (CSA) solutions. We obtained the empirical relationship between the aspect ratio (AR) of CNTs and the ϕ ICP of CNT/CSA solutions using CNT forests fabricated to have a nearly-uniform length. This empirical relationship follows the Onsager scaling ( ϕ ICP  ∼ AR −1 ) and covers a wide range of the AR. Using this relationship, the average length of CNTs can be estimated from the measurement of ϕ ICP . This method is applicable to long CNTs (AR>10 4 ). The accuracy of the method is supported by comparing the results calculated from this method to those obtained from SEM images. This simple yet accurate method may contribute to the controlled growth of CNTs and fabrication of CNT materials that have desired properties. Graphical abstract: Image 1